Patients suffering from psychological impairments following critical illness are in need of information - Vlake, Johan H. (J Intensive Care, 2020)
BACKGROUND: Because critical illness survivors frequently experience several long-term psychological impairments altering quality of life after ICU, there is a trend towards increasing follow-up care, mainly via ICU follow-up clinics. Despite these and other initiatives, understanding of patient’s post-ICU needs to help them cope with their problems and subsequently improve quality of life is largely lacking. Our aim was therefore to assess the needs, expectations and wishes in ICU survivors to receive information with the purpose to help them better grasp ICU treatment. In addition, we assessed the perceived burden of psychological trauma after ICU treatment and the health-related quality of life (HRQoL) up to 2.5 years after ICU discharge. METHODS: In a multicentre, retrospective cross-sectional cohort study, the needs and preferred intervention methods were assessed using a self-composed inventory in adult mechanically ventilated ICU survivors (n = 43). Additionally, the Impact of Event Scale Revised, the Beck Depression Inventory, the EuroQol-5D-5L, and the Short-Form 12 were used to assess psychological burden and HRQoL. RESULTS: A substantial proportion of all ICU survivors (59%, 95% CI 44% to 74%) suffered from psychological impairments after ICU treatment. Seventy-five percent of these patients expressed a wish to receive information, but only 36% desired to receive this information using a commonly used information brochure. In contrast, 71% of these patients had a wish to receive information using a video film/VR. Furthermore, only 33% of these patients was satisfied with the information provided by their treating hospital. Patients with psychological PICS reported a worse HRQoL as compared to a normative Dutch sample (P < 0.001) and as compared to patients without psychological PICS (P < 0.01). CONCLUSIONS: In a Dutch cohort of critical illness survivors, a substantial part of ICU survivors suffer from psychological impairments, such as PTSD and depression, which was associated with a worse HRQoL. These patients are in need of information, have no desire using an information brochure, but are willing to receive information using a video film/virtual reality module. These results support the exploration of such an intervention.